Silver-dichloroquinoline Complexes: Synthesis, Structure and Antitubercular Properties - D’oliveira, Kaíque A.; Glanzmann, Nícolas; Silva, Adilson D. Da; Bruzeguini, Carlos E. T.; Ribeiro, Marcos A.; Canales, Christian S. C. [UNESP]; Roque-borda, Cesar A. [UNESP]; Pavan, Fernando R. [UNESP]; Corbi, Pedro P.; Masciocchi, Norberto; Cuin, Alexandre (Sociedade Brasileira de Química, 2025)
Synthesis, characterization, and antitubercular activity of three silver(I) complexes with 4,7-dichloroquinoline (C9H5Cl2N, DCQ), 2,2’-bipyridine (C10H8N2, Bpy) and triphenylphosphine (C18H15P, PPh3) are presented. Complex 1 was formulated as [Ag(H2O)(DCQ)2(μ-ONO2)Ag(NO3)(DCQ)2], 1:2 M:L1 molar ratio, L1 = DCQ. Complexes 2 [Ag(NO3)(DCQ)(Bpy)] and 3 [Ag(NO3)(DCQ)(PPh3)]2 exhibit 1:1:1 M:L1:L2 molar ratio, where L2 = Bpy or PPh3. All compounds were analytically, spectroscopically, and structurally characterized. The crystal and molecular structures of complexes 1 and 3 were determined by conventional single-crystal X-ray diffraction, while the crystal structure of 2 was elucidated using laboratory powder diffraction method. Elemental analyses, conductometry, infrared (IR), Raman, UV-Vis, and 1H, 13C{1H}, 31P{1H}, {1H-15N} heteronuclear multiple bond correlation (HMBC) nuclear magnetic resonance (NMR) spectroscopies, along with 1H NMR T1 relaxation time measurements, corroborate the proposed formulas. Complex 3, in the solid state, was found to contain significant residual solvents (CH3OH and CH3CN). Consequently, its desolvation process was investigated using IR microscopy and X-ray powder diffraction. In vitro biological assays against Mycobacterium tuberculosis H37Rv (ATCC 27294) were performed for all compounds. Complexes 1 and 3 shown the lowest concentration of the antibiotic at which 90% of the isolates are inhibited (MIC90) of 7 ± 1 and 14 ± 3 µg mL-1, suggesting their potential as antimycobacterial agents, in contrast, assays indicate lower activity for compound 2 against the evaluated strains.
Keywords: 4,7-dichloroquinoline; homo/heteroleptic complexes; silver complexes; Mycobacterium tuberculosis